Full autopsy in a confirmed COVID-19 patient in Lagos, Nigeria - A case report - Samuel Olalekan Keshinro, MBChB, FMCPath, DipFHID; Nicholas Awodele Awolola, MBBS, FMCPath; Luqman Adedotun Adebayo, MBBS, FMCPath; Wasiu Bamidele Mutiu, MBBS, FMCPath; Babatunde Akeem Saka, DVM, PhD; Ismail Adeshina Abdus-Salam, MBBS, MPH, FMCPH&CM (Elsevier, 2021)
Objectives: To report the postmortem findings of a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) positive individual who died in Lagos (Nigeria) in June 2020 and to investigate the cause, pathogenesis as well as pathological changes noticed during the examination. Methods: Complete postmortem examination was performed according to standard procedures in a regular autopsy suite using personal protective equipment including N95 masks, goggles and disposable gowns. The diagnosis of coronavirus disease 2019 (COVID-19) was confirmed by real-time reverse transcription polymerase chain reaction (RT-PCR) testing on postmortem nasopharyngeal swabs. Results: A 47-year-old man with a medical history of well controlled hypertension and dyslipidaemia died after long hours of transportation for medical care in a hospital in Lagos. He tested positive for SARS-CoV-2 on ante- and postmortem nasopharyngeal swabs. Autopsy revealed pneumonia with diffuse alveolar damage, disseminated intravascular coagulopathy and hypovolaemic shock. Conclusions: Autopsy can be performed on decedents who died from or with SARS-CoV-2 infection in a low resource environment such as ours. A standard autopsy room was used while deploying recommended infection prevention control and regular decontamination. The clinical details, autopsy findings such as diffuse alveolar damage and airway inflammation were consistent with a COVID-19 related pathology. While the decedent had 'controlled' co-morbidity, he succumbed to multi-organ failure occasioned by shock and disseminated intravascular coagulopathy.